2009
DOI: 10.1016/j.nlm.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Some surprising findings on the involvement of the parietal lobe in human memory

Abstract: The posterior parietal lobe is known to play some role in a far-flung list of mental processes: linking vision to action (saccadic eye movements, reaching, grasping), attending to visual space, numerical calculation, and mental rotation. Here we review findings from humans and monkeys that illuminate an untraditional function of this region: memory. Our review draws on neuroimaging findings that have repeatedly identified parietal lobe activations associated with short-term or working memory and episodic memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
128
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 144 publications
(195 reference statements)
10
128
0
Order By: Relevance
“…Consistent with this idea of retrieval, Silk et al (2010) have suggested that the motor planning map retained by neural activity in the right SMG is used as a basis for the control of attentional shifts. This highlights the close association that has been found to exist between the mechanisms of memory and attention in the PPC proposed by many studies (Jonides, Smith, Koeppe, Awh, Minoshima & Mintun, 1993;Smith & Jonides, 1997;Courtney, Ungerleider, Keil & Haxby, 1997;Vandenburgh et al, 1996;Nobre et al, 1997;Ungerleider, Courtney & Haxby, 1998;Kessels, d'Alfonso, Postma & de Haan, 2000;Corbetta et al, 2000;Hussain et al, 2001;Rizzolatti & Matelli, 2003: Koch, Oliveri, Torriero, Carlesimo, Turriziani & Caltagirone, 2005Curtis, 2006;Van Asselen, Kesseks, Neggers, Kapelle, Frijns & Postma, 2006;Berryhill & Olson, 2008a,b;Olson & Berryhill, 2009;Cabeza, Ciaramelli & Moscovitch, 2012;Corbetta & Shulman, 2002;Singh-Curry & Husain, 2009). One view is that attention and memory rely upon overlapping cortical networks sharing common neural resources within the PPC (Awh, Jonides & Reuter-Lorenz, 1998;Awh, Vogel & Oh, 2006;Postle Awh, Jonides, Smith & D'Esposito, 2004;Theeuwes, Belopolsky & Olivers, 2009).…”
Section: Dorso-parietal Versus Ventro-parietal Processing Pathwayssupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with this idea of retrieval, Silk et al (2010) have suggested that the motor planning map retained by neural activity in the right SMG is used as a basis for the control of attentional shifts. This highlights the close association that has been found to exist between the mechanisms of memory and attention in the PPC proposed by many studies (Jonides, Smith, Koeppe, Awh, Minoshima & Mintun, 1993;Smith & Jonides, 1997;Courtney, Ungerleider, Keil & Haxby, 1997;Vandenburgh et al, 1996;Nobre et al, 1997;Ungerleider, Courtney & Haxby, 1998;Kessels, d'Alfonso, Postma & de Haan, 2000;Corbetta et al, 2000;Hussain et al, 2001;Rizzolatti & Matelli, 2003: Koch, Oliveri, Torriero, Carlesimo, Turriziani & Caltagirone, 2005Curtis, 2006;Van Asselen, Kesseks, Neggers, Kapelle, Frijns & Postma, 2006;Berryhill & Olson, 2008a,b;Olson & Berryhill, 2009;Cabeza, Ciaramelli & Moscovitch, 2012;Corbetta & Shulman, 2002;Singh-Curry & Husain, 2009). One view is that attention and memory rely upon overlapping cortical networks sharing common neural resources within the PPC (Awh, Jonides & Reuter-Lorenz, 1998;Awh, Vogel & Oh, 2006;Postle Awh, Jonides, Smith & D'Esposito, 2004;Theeuwes, Belopolsky & Olivers, 2009).…”
Section: Dorso-parietal Versus Ventro-parietal Processing Pathwayssupporting
confidence: 56%
“…The PPC is commonly divided into the superior parietal lobe (SPL) which lies dorsal to the intra-parietal sulcus (IPS), and the more ventral inferior parietal lobe (IPL), which comprises the angular gyrus (AG), the supramarginal gyrus (SMG) and the temporo-parietal junction (TPJ) Olson & Berryhill, 2009;Hutchinson et al, 2009). Accurate targeting of each subject's right SMG for TMS was achieved using procedures previously described by this and other laboratories (Sack et al, 2009;McKeefry et al, 2008) using a 3-D ultrasound digitizer CMS30P (Zebris, Tübingen, Germany) in conjunction with the BrainVoyager QX software (version 2.0 Brain Innovation, Netherlands).…”
Section: Selection and Identification Of Areas For Tmsmentioning
confidence: 99%
“…Because this region is consistently implicated in a vast array of tasks--from attention and numerical cognition to decision-making and action intention--it has proven difficult to identify the shared and distinct computational processes supported by PPC that account for its participation in these widely varied domains. Recently, memory researchers have also turned their attention to the role of PPC in cognition because human neuroimaging experiments have consistently revealed PPC activity during episodic retrieval (Wheeler and Buckner 2004;Wagner et al 2005;Cabeza et al 2008;Ciaramelli et al 2008;Vilberg and Rugg 2008b;Olson and Berryhill 2009). Moreover, studies of human patients with lesions to PPC have revealed subtle, but significant, memory impairments (Berryhill et al 2007;Davidson et al 2008;Berryhill et al 2010;Ciaramelli et al 2010;Drowos et al 2010; Simons et al 2010, cf.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the neural mechanism of action of WMT in 2 modestly sized functional magnetic resonance imaging studies in healthy adults (n03 and n08) in Olesen et al [35] and (n03) in Westerberg and Klingberg [41] suggest that WMT increases brain activity in the PFC and parietal cortex [35], regions frequently associated with WM processing and executive functioning in general [42,43]. A functional magnetic resonance study of training in ADHD using a broad package of exercises [44], focusing on response inhibition and selective attention rather than WM, found increased frontal, middle temporal, and cerebellar activity after training.…”
Section: Introductionmentioning
confidence: 99%